Antigen-Engaged B Cells Undergo Chemotaxis toward the T Zone and Form Motile Conjugates with Helper T Cells - Okada, Takaharu; Miller, Mark J; Parker, Ian; Krummel, Matthew F; Neighbors, Margaret; Hartley, Suzanne B; O'Garra, Anne; Cahalan, Michael D; Cyster, Jason G (PLoS biology, 2005)
Interactions between B and T cells are essential for most antibody responses, but the dynamics of these interactions are poorly understood. By two-photon microscopy of intact lymph nodes, we show that upon exposure to antigen, B cells migrate with directional preference toward the B-zone-T-zone boundary in a CCR7-dependent manner, through a region that exhibits a CCR7-ligand gradient. Initially the B cells show reduced motility, but after 1 d, motility is increased to approximately 9 microm/min. Antigen-engaged B cells pair with antigen-specific helper T cells for 10 to more than 60 min, whereas non-antigen-specific interactions last less than 10 min. B cell-T cell conjugates are highly dynamic and migrate extensively, being led by B cells. B cells occasionally contact more than one T cell, whereas T cells are strictly monogamous in their interactions. These findings provide evidence of lymphocyte chemotaxis in vivo, and they begin to define the spatiotemporal cellular dynamics associated with T cell-dependent antibody responses.